Letter (copy) : Help for the Spanish Workers! - Tewson, Vincent
028-0244-001 Our Ref: HVT/FC/795. 29th July, 1936. Mr. R. F. Lancaster, Secretary, The Co-operative Wholesale Society Ltd., 1, Balloon Street, MANCHESTER. Dear Mr. Lancaster, HELP FOR THE SPANISH WORKERS! You will be aware that the National Council of Labour have opened an appeal to assist in the relief of Spanish workers and their dependents suffering in the present unfortunate events in Spain. I am enclosing for your information copy of a circular which has been issued to our affiliated bodies and I am asked to make an approach to the C.W.S. Directors requesting that consideration be given to the possibility of assisting the Fund. The National Council feel confident that your Board will be in complete sympathy with the struggle against Fascism in Spain, and any financial assistance which they can render will be very deeply appreciated. Yours sincerely, for Joint Secretary. Circular. 292/946/28/244